2003
DOI: 10.1074/jbc.m210412200
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of GDP Dissociation Inhibitor and Membrane Translocation Are Required for Efficient Activation of Rac by the Dbl Homology-Pleckstrin Homology Region of Tiam

Abstract: Small G proteins of the Rho/Rac/Cdc42 family are associated with lipid membranes through their prenylated C termini. Alternatively, these proteins form soluble complexes with GDI proteins. To assess how this membrane partitioning influences the activation of Rac by guanine nucleotide exchange factors, GDP-to-GTP exchange reactions were performed in the presence of liposomes using different forms of Rac-GDP. We show that both non-prenylated Rac-GDP and the soluble complex between prenylated Rac-GDP and GDI are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 35 publications
7
61
0
Order By: Relevance
“…However, Dbl-catalyzed nucleotide exchange is inhibited by RhoGDI in the absence of membranes (Yaku et al, 1994). Additionally, membrane-bound Rac is a better substrate for Tiam1 than soluble Rac (Robbe et al, 2003). These results suggest that partial or complete dissociation of the Rho GTPase/ RhoGDI complex precedes and is required for activation by GEFs.…”
Section: Introductionmentioning
confidence: 61%
“…However, Dbl-catalyzed nucleotide exchange is inhibited by RhoGDI in the absence of membranes (Yaku et al, 1994). Additionally, membrane-bound Rac is a better substrate for Tiam1 than soluble Rac (Robbe et al, 2003). These results suggest that partial or complete dissociation of the Rho GTPase/ RhoGDI complex precedes and is required for activation by GEFs.…”
Section: Introductionmentioning
confidence: 61%
“…Current models of TIAM function hypothesize that TIAM1 recruits and activates Rac1 at the cytosolic surface of the plasma membrane. 33 As platelet activation increases the association of TIAM1 with Rac1 and phosphorylated S6K1 ( Figure 2D), TIAM1 may recruit a Rac1-S6K1 complex to the plasma membrane to help drive lamellipodia formation. In support of this model, confocal microscopy revealed that TIAM1 colocalized with Rac1 at the lamellipodial edge of activated platelets ( Figure 2E).…”
Section: Discussionmentioning
confidence: 99%
“…As seen in Figure 2C, Rac1-GST captured S6K1 from platelet lysates while GST alone failed to interact with S6K1. Previous work has established that Rac1 activity in tumor cells is regulated in part by TIAM1, 33 a Rac guanine nucleotide exchange factor (GEF) that is known to interact with S6K1. 34 To determine whether S6K1 and Rac1 are associated with TIAM1 in platelets, we next immunoprecipitated TIAM1 from platelet lysates with sc-872, an antibody that specifically captures TIAM1 from platelet lysates (supplemental Figure 3).…”
Section: S6k1 and Rac1 Colocalize At The Leading Edge Of Activated Plmentioning
confidence: 99%
“…RhoGDI retains Rac into the cytoplasm and must dissociate to allow Rac to encounter its GEFs. 32,33 Recently, Price et al 34 have shown that Ca 2ϩ induces a disruption of the RacRhoGDI complex leading to the translocation and activation of Rac in PC3 cells. Thus, one could speculate that such a mechanism might occur in cardiomyocytes and contribute to Epac-induced Ca 2ϩ -dependent Rac activation We report for the first time to our knowledge that Epac is implicated in the activation of NFAT in cardiac myocytes.…”
Section: Discussionmentioning
confidence: 99%